Factors Impacting Airport Performance: the Case of Prishtina and Tirana - Abdullahu, Lorik; Reshidi, Nail (Ekonomika, 2018)
[full article and abstract in English]The market liberalization, airport privatization and increased number of low-cost carriers have significantly affected airport performance lately. The aim of this study is to determine and analyze passengers’ demographics and their interaction with the external macro environment by providing empirical evidence of their impact on airport performance. The combined two-group proportion test and loglinear analysis were applied as the main analytical methods, whereas a PESTEL analysis was used as an auxiliary tool to help explain quantitative findings. The results show that due to a large diaspora and difficult socioeconomic situation, there is a gap for more direct point-to-point flights offered by the low-cost carriers in general and, more specifically, if more direct flights are being offered from Prishtina Airport, their likelihood ratio is to increase twice in its absolute value, whereas in Tirana Airport, their likelihood ratio is to increase twice if they offer more connection flights. This confirms the conclusion that there is a gap for additional services to be provided, which could significantly affect the airport performance in return. In the end, this study also raises a new hypothesis: whether the younger generation of the diaspora, members of which were born and educated abroad, will negatively affect airport performance due to their decreasing tendency and interest to visit the homeland of their parents.
Keywords: airport; passengers; demographics, services